Celebrity Endorsement to Fascinate Consumer Purchase Intention: Negotiating Role of Brand Loyalty - Imtiaz Hussain; Muhammad Noman Qaisar; Dr. Muhammad Hashim; Ali Hadi Rabbani; Clive Asuai (Dialogue Social Science Review (DSSR), 2025)
This study explores the impact of celebrity endorsement on consumer purchase intention, with brand loyalty serving as a mediating factor. The increasing use of celebrities in marketing has raised questions about how their influence affects consumer behavior, particularly about brand perception and purchase decisions. Using a quantitative approach, the research surveyed 200 respondents to examine the relationships between celebrity endorsement, brand loyalty, and purchase intention. The results show a significant positive correlation between celebrity endorsement and both brand loyalty and purchase intention. Additionally, brand loyalty was found to play a key mediating role in the relationship between celebrity endorsement and purchase intention, indicating that consumers who are loyal to a brand are more likely to purchase endorsed products. The study supports the idea that celebrity endorsement not only enhances consumer awareness but also builds emotional connections with brands, fostering long-term loyalty. These findings have important implications for marketers, suggesting that brands should carefully select endorsers who align with their identity and values to foster deeper consumer engagement. This research contributes to the understanding of how celebrity endorsements influence consumer behavior, offering insights into the complex interplay between endorsement, loyalty, and purchase intention. Future research could explore the effects of different types of celebrities and endorsements across various consumer segments.